Incidence and Post-Operative Visual Outcome in Patients with Intraocular Foreign Body - Ejaz Ahmed Javed; Muhammad Usama Javed; Syed Jahanzaib Naqvi; Zafar Ali Chaudhary (Pakistan Journal of Medical Research, 2024)
Background: Intraocular foreign body is an important complication of ocular trauma, especially open globe trauma. It can cause a range of complications leading to severe visual impairment to permanent blindness. They are removed via Pars Plana Vitrectomy using either forceps, endomagnet, or both. Various management techniques and their impact on final visual outcomes are identified in this study.